Influence Analysis Expenditure Zakat, Infak Welfare and Charity Against Muzakki (Studies In Baznas In West Lombok Regency) - Asdiansyuri, Ulfiyani (Institute of Research and Community Service, University of Brawijaya, 2016)
The aims of this research is to analyze 1) influence factors of individual characteristics as age, marital status, education, number of dependents, income, and understanding values of religious that owned by muzakki against of spending Zakat, Infak and Sedekah (ZIS), and 2) influence factors of individual characteristics such as age, marital status, education, number of dependents, income, and understanding values of religious that owned by muzakki against muzakkiâ€™s welfare through spending Zakat, Infak and Sedekah (ZIS). Estimation techniques using validity, the reliability, classical assumption test and path analysis test. The result shows 1) there are influences such as marital status, education, income and religious values against spending Zakat, Infak and Sedekah (ZIS) by a muzakki, and 2) the effect of age, educqation, number of dependents, income and religious values affect muzakkiâ€™s welfare by spending through Zakat, Infak and Sedekah (ZIS).Â Keywords: Individual Characteristics, ValuesReligious, Zakat expenditures, Infak and Sedekah (ZIS), Welfare Muzakki.